ROLE OF TECHNOLOGY ACCEPTANCE MODEL (TAM) TOWARDS THE TOURISM OF EASTERN PROVINCE GROUP - Anuwichanont, Jirawat; Mechinda, Panisa; Kanraweekultana, Natratanon (RMUTT Global Business and Economics Review, 2023)
The objective of this research was to examine the factors influencing the acceptance of online social media for tourism and future intention to travel in the eastern province group. This research was quantitative research method. The population consisted of Thai tourists who used to travel in the eastern province group. The sample included 400 Thai tourists and 100 tourists per province which were recruited by the convenience sampling. The questionnaire was used as the tool for data collection. The questionnaire was examined in terms of the content validity and reliability. The Factor Analysis, Confirmatory Factor Analysis and Structural Equation Model were employed for hypotheses testing to examine the statistically significant relationships between the variables. The research findings revealed that 1) The perceived ease of use and resource availability influenced the acceptance of online social media for tourism at the statistical significance level of .001. 2) The acceptance of online social media for tourism influenced the future intention to travel at the statistical significance level of .001. However, perceived usefulness was not found to influence the acceptance of online social media for tourism. These findings were utilized to develop the marketing communication through online social media to promote the tourism in the eastern province group.